Metamaterials: Diatom Frustule‐Inspired Metamaterial Absorbers: The Effect of Hierarchical Pattern Arrays (Adv. Funct. Mater. 22/2019). (27th May 2019) - Li, Aobo; Zhao, Xiaoguang; Duan, Guangwu; Anderson, Stephan; Zhang, Xin
Abstract : In article number1809029, Xin Zhang and co‐workers use a hierarchical hexagonal design of nanoresonators to realize a near‐infrared metamaterial absorber, inspired by the hierarchical design of diatom frustule pores. With this method, an additional degree of freedom (hierarchy) has been introduced into the design of electromagnetic metamaterials. The results from experiments, numerical simulations, and analytical calculations demonstrate that such a design yields a widened high‐absorption band in the spectrum.